2020
DOI: 10.3389/fpls.2019.01743
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Role of Glutamate in Plants

Abstract: It is well known that glutamate (Glu), a neurotransmitter in human body, is a protein amino acid. It plays a very important role in plant growth and development. Nowadays, Glu has been found to emerge as signaling role. Under normal conditions, Glu takes part in seed germination, root architecture, pollen germination, and pollen tube growth. Under stress conditions, Glu participates in wound response, pathogen resistance, response and adaptation to abiotic stress (such as salt, cold, heat, and drought), and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(129 citation statements)
references
References 87 publications
(173 reference statements)
2
127
0
Order By: Relevance
“…While both tissues of Ispir accumulated glutamate, TR43477 tissues accumulated glutamine, which indicates an inequality in the reaction direction for these varieties. Glutamate is essential for stress tolerance as it was demonstrated to support amino-acid synthesis under osmotic stress ( Ramos et al, 2005 ), activate stress tolerance pathways via H 2 O 2 burst ( Lei et al, 2017 ), act as a signaling molecule for stress response pathways ( Kan et al, 2017 ) and regulate the stomatal aperture under low-water conditions ( Yoshida et al, 2016 ; Qiu et al, 2020 ). Glutamate is also necessary for biosynthesis of glutathione, an active compound of antioxidant defense system ( Lu, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…While both tissues of Ispir accumulated glutamate, TR43477 tissues accumulated glutamine, which indicates an inequality in the reaction direction for these varieties. Glutamate is essential for stress tolerance as it was demonstrated to support amino-acid synthesis under osmotic stress ( Ramos et al, 2005 ), activate stress tolerance pathways via H 2 O 2 burst ( Lei et al, 2017 ), act as a signaling molecule for stress response pathways ( Kan et al, 2017 ) and regulate the stomatal aperture under low-water conditions ( Yoshida et al, 2016 ; Qiu et al, 2020 ). Glutamate is also necessary for biosynthesis of glutathione, an active compound of antioxidant defense system ( Lu, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In both species, the methionine biosynthesis was reduced. In terrestrial plants, the increased levels in some of these amino acids have previously been shown to be triggered by abiotic stress [ 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…This compound is primarily biosynthesized from pyruvate generated from the glycolytic pathway (Chesworth et al, 1998), through the breakdown of photosynthates arising from the Calvin cycle (Michelet et al, 2013). Pyruvate (C 3 H 4 O 3 ) is converted to 2-oxoglutarate (α-ketoglutarate) through the action of glutamate dehydrogenase (GDH) in the tricarboxylic acid (TCA) cycle (Qiu et al, 2019). Glutamate is also synthesized through the proline (Pro)/pyrroline 5-carboxylate (P5C) cycle in the plant cytoplasm (Miller et al, 2009;Qiu et al, 2019).…”
Section: Nitrogen Acquisition In Host Plantsmentioning
confidence: 99%
“…Pyruvate (C 3 H 4 O 3 ) is converted to 2-oxoglutarate (α-ketoglutarate) through the action of glutamate dehydrogenase (GDH) in the tricarboxylic acid (TCA) cycle (Qiu et al, 2019). Glutamate is also synthesized through the proline (Pro)/pyrroline 5-carboxylate (P5C) cycle in the plant cytoplasm (Miller et al, 2009;Qiu et al, 2019). Glutamate is then used in nitrogen acquisition systems.…”
Section: Nitrogen Acquisition In Host Plantsmentioning
confidence: 99%